Analisis Putusan Hakim Tentang Izin Poligami dengan Dalih Post-Partum Depression dan Anxiety Disorder (Studi Putusan No. 366/Pdt.G/2023/PA.Ska) - Ruslan Arifin; Muhammad Kurniawa Budi Wibowo; Aditya Fajri Kurnia Pradana (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2024)
A license to practice polygamy was granted by the Surakarta Religious Court in case number 366/Pdt.G/2023/PA.Ska. The respondent's postpartum depression and anxiety disorders were the cause of this decision. Nevertheless, these requirements are not fully explained by the laws regulating polygamy, such as Article 57 KHI and Article 4 paragraph (2) of the Marriage Law. The author of this paper examines the legal factors that judges at the Surakarta Religious Court took into account while making their decision in case number 366/Pdt.G/2023/PA.Ska. Prescriptive normative research methodology is employed in this study, which collects primary and secondary data. The primary focus of this research is secondary data gathered from a review of the literature. The findings demonstrated that the court based the facultative requirements in polygamy instances on Article 4 paragraph (2) of the Marriage Law. In addition, judges also use the principle of benefit to accept polygamy applications. In this case, the judge considered the benefits of polygamy rather than limiting the number of wives, unless the wife suffered from mental disorders after giving birth